Management of Gastric Motility Disorder - Mustika Dian Permana; Kaka Renaldi (The Indonesian Society for Digestive Endoscopy, 2018)
Gastric motility disorder or gastroparesis is an objective slowing of gastrointestinal emptying syndrome, in the absence of mechanical obstruction, with cardinal symptoms such as rapid feeling of fullness, fullness sensation after eating, nausea, vomiting, bloating, and upper abdominal pain. Patients with gastroparesis are at risk of weight loss, malnutrition, and lack of vitamins and minerals, as well as increasing morbidity and mortality. The prevalence and incidence data of gastroparesis do not describe the true reality, because of the complexity of diagnosis. Beside Diabetes mellitus, many other causes should also be considered. Several studies have shown that nausea, vomiting and fullness sensation in abdominal are the most associated symptoms with gastroparesis. A 4-hour solid phase gastric emptying scintigraphy is the diagnostic standard for the slowing of gastric emptying. Lowest effective dose metoclopramide starting with a dose of 3 x 5 mg is the first line for pharmacological therapy. For persistent or refractory gastroparesis with pharmacologic therapy, gastric electrical stimulation (GES) and surgical therapy may be considered. The management should involve relevant medical team by not forget to consider patient comfort.